2009
DOI: 10.1016/j.tsf.2008.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Structure and optical properties of ZnO:V thin films with different doping concentrations

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited.In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(30 citation statements)
references
References 20 publications
5
25
0
Order By: Relevance
“…It has been observed that the XRD peak broadening decreases with increase of growth temperature. The peaks with the Miller indices given belong to the ZnO presence of five peaks with orientations; (100), (002), (102), (220) and (110) confirmed these X-ray diffraction patterns are polycrystalline for ZnO thin films deposited on silicon [7]. The intensity of these diffraction increases with increasing the growth temperature.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…It has been observed that the XRD peak broadening decreases with increase of growth temperature. The peaks with the Miller indices given belong to the ZnO presence of five peaks with orientations; (100), (002), (102), (220) and (110) confirmed these X-ray diffraction patterns are polycrystalline for ZnO thin films deposited on silicon [7]. The intensity of these diffraction increases with increasing the growth temperature.…”
Section: Resultssupporting
confidence: 54%
“…, where λ, θ and B are the X-ray wavelength (1.54 Å), Bragg diffraction angle and line of full width at half maximum, respectively [7]. It was determined that there is a continuous increase in particle size with increasing growth temperature.…”
Section: Cos D Bmentioning
confidence: 99%
See 1 more Smart Citation
“…For lower concentration (1-5 %), the homogeneity can be seen but for higher concentration inhomogeneous distribution is evident. As doping concentration is large, it causes inhomogeneity and destroys the crystal structure (Wang et al 2009) as can be observed for 9 % doped sample. There is a large difference in particle size of pure and the 1 % V doped sample which indicates that even a small amount of V doping causes a significant change in the morphology.…”
Section: Scanning Electron Microscopy Semmentioning
confidence: 81%
“…Finally, the dislocation density (δ) which is given by the following relation: between cycles of preparation this film [32]. In the same line, in the UV region, it can be seen shoulders, lying in transmission spectra which may be assigned to the presence of porosity and defaults inside the films.…”
Section: Structural Propertiesmentioning
confidence: 88%